Macroeconomic variables towards net asset value of sharia mutual funds in Indonesia and Malaysia - Riwi Sumantyo; Dessy Anis Savitri (Jurnal Keuangan dan Perbankan, 2019)
Sharia mutual fund as one of the investment instruments in sharia capital market shows significant development. There are various factors that may influence, among these factors are macroeconomic variables. This research aims to analyze the effect of macroeconomic factors on the development of sharia capital market industry. Macroeconomic variables that are used is the money supply (M1), Gross Domestic Product (GDP), and inflation.  The data used in this research is a quarterly money supply data, GDP, and inflation from January 2012 to December 2016. The methods used to analyze regression data is the data panel. The results of the analysis showed that all of the independent variable used in this study i.e. the money supply (M1), GDP, and inflation has a positive influence and significance to the Net Asset Value (NAV) mutual funds sharia in Indonesia and Malaysia. These results can provide a sound contribution for further research, government, management of the company, and investors regarding the Net Assets Value mutual funds sharia in Indonesia and Malaysia.JEL Classification: D51, E43, F41, G15DOI: https://doi.org/10.26905/jkdp.v23i2.2195